2016
DOI: 10.1111/jcmm.12865
|View full text |Cite
|
Sign up to set email alerts
|

Lentinan protects pancreatic β cells from STZ‐induced damage

Abstract: Pancreatic β‐cell death or dysfunction mediated by oxidative stress underlies the development and progression of diabetes mellitus (DM). In this study, we evaluated the effect of lentinan (LNT), an active ingredient purified from the bodies of Lentinus edodes, on pancreatic β‐cell apoptosis and dysfunction caused by streptozotocin (STZ) and the possible mechanisms implicated. The rat insulinoma cell line INS‐1 were pre‐treated with the indicated concentration of LNT for 30 min. and then incubated for 24 hrs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 54 publications
6
23
0
Order By: Relevance
“…The decreased ratio of Bax to Bcl-2 and suppressive cleavage of caspase-3 by LEN in hypoxia-treated cell indicated that LEN inhibited cell apoptosis to some extent. Our results are consistent with the previous study that LEN protects pancreatic b cells from streptozotocin-induced injury [26].…”
Section: Discussionsupporting
confidence: 94%
“…The decreased ratio of Bax to Bcl-2 and suppressive cleavage of caspase-3 by LEN in hypoxia-treated cell indicated that LEN inhibited cell apoptosis to some extent. Our results are consistent with the previous study that LEN protects pancreatic b cells from streptozotocin-induced injury [26].…”
Section: Discussionsupporting
confidence: 94%
“…The primary structure of Lentinan (400-800 kDa) contains five (1!3)-b-glucose residues in a linear linkage and two (1!6)-b-glucopyranoside side chains (Zhang et al, 2001). Lentinan can protect against pancreatic b-cell apoptosis and dysfunction by inhibiting ROS generation and exhibits antiapoptotic effects by preventing JNK and p38 MAPK signaling or/and antidysfunction effects by preventing NF-kB activation (Zhang et al, 2016). Krestin (94 kDa), also known as Coriolus versicolor polysaccharide, is a b-glucan-protein complex made up of approximate 25-38% protein residues.…”
Section: Structure-activity Relationship Of Mushroom Polysaccharidesmentioning
confidence: 99%
“…Lentinan, a well-known medicinal fungal polysaccharide, is a glucan produced by the edible mushroom Lentinus (or Lentinula ) edodes , and has been widely used as a component of traditional diets and medicine in Asia for hundreds of years [ 11 ]. Previous studies have shown that lentinan has hypolipidemic and hypoglycemic effects in cell culture experiments [ 12 , 13 ]. Flos Lonicera , another widely used medicinal and edible herb, also has hepatoprotective, antihypertensive, anti-inflammatory, antioxidative and antiviral activities [ 8 , 14 , 15 ], and Flos Lonicera polysaccharides (FLP) was reported to have a wide range of pharmacological effects, such as antioxidant and antiallergy effects [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%